THE NEXUS BETWEEN CHILD ABUSE AND ECONOMIC CONDITIONS: EMPIRICAL EVIDENCE FROM MALAYSIA - Zainal, Nurazilah; Hitam, Mizan; Md Zin, Norlaila; R. Vijayarajoo, Angeline Ranjethamoney; Senturk, Recep (PLANNING MALAYSIA, 2023)
This research attempts to examine the impact of economic conditions on number of child abuse cases in Malaysia. Yearly time series data has been included in data collection from year 1988 until 2019. To achieve the objective of the study, an estimation method of Autoregressive Distributed Lagged (ARDL) has been employed. The ARDL methodology consists of two steps analysis; first, ARDL Bound test which to determine the existence of cointegration relationship between child abuse and economics condition and second, ARDL Level Relation test with purpose to identify the cointegration relationship does significant in the long run. The findings have found cointegration relationship among the variables. However, only inflation (INF), unemployment (UEM), and minimum wage (MIN) appear significant to affect number of child abuse cases in Malaysia in the long run. The results suggest except poverty (POV), the number of child abuse cases in Malaysia are fully adjusted by the movement in INF, UEM and MIN. Overall, output from this study provide recommendation for policy-makers in readjusting the existing policies so that they able to curb the rising number of child abuse as well as to promotes economic growth and peaceful environment in Malaysia.